2002
DOI: 10.1002/mus.10250
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin receptor reduction in skin and fibroblasts of patients with Ullrich's disease

Abstract: Ullrich's disease is a congenital muscular dystrophy characterized clinically by generalized muscle weakness, multiple contractures of the proximal joints, and hyperextensibility of the distal joints. Recent studies have demonstrated that collagen VI is deficient in the muscles of patients with Ullrich's disease, and some cases result from recessive mutations of the collagen VIalpha2 gene (COL6A2). Fibronectin is one of the main components of the extracellular matrix (ECM) and associates with a variety of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Ten possible candidate genes were considered on the basis of the following criteria: either i) their direct interaction with collagen VI, as in the case of HSPG2 [13], ITGA1, ITGA2, ITGB1 [14], DNC and BGN [15]; ii) their secondary involvement in collagen VI-deficient tissues, as in NG2-proteoglycan [16,17], ITGA5 and ITGA7 [18,19], or iii) their mutations causing an overlapping phenotype with collagen VI-related myopathies, as in TNXB [20]. COL6A5 (COL29A1) and COL6A6, which are expressed in skeletal muscle, were also included since collagen VI alpha1-deficient mice do not express collagen VI alpha 5 or alpha 6 chains [21].…”
Section: Resultsmentioning
confidence: 99%
“…Ten possible candidate genes were considered on the basis of the following criteria: either i) their direct interaction with collagen VI, as in the case of HSPG2 [13], ITGA1, ITGA2, ITGB1 [14], DNC and BGN [15]; ii) their secondary involvement in collagen VI-deficient tissues, as in NG2-proteoglycan [16,17], ITGA5 and ITGA7 [18,19], or iii) their mutations causing an overlapping phenotype with collagen VI-related myopathies, as in TNXB [20]. COL6A5 (COL29A1) and COL6A6, which are expressed in skeletal muscle, were also included since collagen VI alpha1-deficient mice do not express collagen VI alpha 5 or alpha 6 chains [21].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we found a marked reduction of fibronectin receptors in the skin and cultured fibroblasts of two patients with Ullrich's disease with collagen VI deficiency. We speculated that collagen VI deficiency may lead to a reduction of fibronectin receptors and that an abnormality of cell adhesion may be involved in the pathogenesis of Ullrich's disease 17. Recently, we evaluated the role of nonsense‐mediated mRNA decay (NMD) in Ullrich's disease and found that the pharmacological block of NMD caused upregulation of the mutant collagen VI, resulting in upregulation of the fibronectin receptor and partially functional ECM formation 34.…”
Section: Discussionmentioning
confidence: 99%
“…In some UCMD cases collagen VI is completely absent from skin, while in others it may be only reduced or even look normal [117,118]. There is one report of reduced fibronectin receptor expression in the dermis of a UCMD skin biopsy [119]. Primary fibroblasts can be induced to secrete collagen VI in vitro using ascorbic acid in the medium.…”
Section: Diagnosismentioning
confidence: 97%